Complexity in the Evolution, Composition, and Spectroscopy of Brown Carbon in Aircraft Measurements of Wildfire Plumes. Issue 9 (5th May 2022) - Washenfelder, R. A.; Azzarello, L.; Ball, K.; Brown, S. S.; Decker, Z. C. J.; Franchin, A.; Fredrickson, C. D.; Hayden, K.; Holmes, C. D.; Middlebrook, A. M.; Palm, B. B.; Pierce, R. B.; et al.
Abstract: Biomass burning is a major source of light‐absorbing organic aerosol (brown carbon), but its composition, chemical evolution, and lifetime are not well known. We measured water‐soluble brown carbon absorption from 310 to 500 nm on the National Oceanic and Atmospheric Administration Twin Otter aircraft during flights downwind of western United States wildfires in summer 2019. The sampling strategy was near‐Lagrangian and the plume ages spanned 0–5 hr. Trends in brown carbon mass absorption coefficient with plume age varied between flights, and did not show an exponential decay over these short time scales. The measured absorption spectra were smoothly varying, without identifiable contributions from individual chromophores with structured absorption. Using aerosol tracer ions and reference absorption spectra, the calculated contribution of 4‐nitrocatechol to total absorption was <22 ± 9% and <11 ± 5%, although spectral fitting showed that it may be as low as <1.1% and <0.6% at 365 and 405 nm, respectively. Plain Language Summary: Wildfires are a major source of light‐absorbing particles that affect the Earth's radiative budget, but the lifetime and composition of these particles are not well known. We measured the light absorption and concentration of water‐soluble organic aerosol during aircraft flights through wildfire smoke plumes that were less than 5 hr old. We found that light absorption does not decrease over these short time scales, and may instead increase or remain constant. We examined the absorption spectra and aerosol composition to determine the contribution of individual species to the total absorption by organic aerosol. Key Points: Dilution‐normalized biomass burning brown carbon showed variable, non‐exponential trends over 5 hr, contrary to recent parameterizations Spectral fits constrain the contribution of 4‐nitrocatechol to brown carbon absorption to be <1.1% at 365% and <0.6% at 405 nm Absorption spectra indicate a complex mixture of absorbing compounds without identifiable contributions from individual chromophores